1999
DOI: 10.2337/diabetes.48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in diabetic complications: a new perspective on an old paradigm.

Abstract: Oxidative stress and oxidative damage to tissues are common end points of chronic diseases, such as atherosclerosis, diabetes, and rheumatoid arthritis. The question addressed in this review is whether increased oxidative stress has a primary role in the pathogenesis of diabetic complications or whether it is a secondary indicator of end-stage tissue damage in diabetes. The increase in glycoxidation and lipoxidation products in plasma and tissue proteins suggests that oxidative stress is increased in diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
1,459
3
62

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,171 publications
(1,559 citation statements)
references
References 46 publications
35
1,459
3
62
Order By: Relevance
“…The recognition of NEG as a molecular mechanism that contributes to the development of OA provides new opportunities for therapies directed at the prevention of OA by inhibiting or reversing AGE formation. Inhibition of AGE formation by prophylactic treatment with compounds such as aminoguanidine, pyridoxamine, tenilsetam, or simple amino acids (e.g., lysine or arginine) has been shown to prevent AGErelated pathologies such as vascular stiffening, heart collagen accumulation, and protein crosslinking (59)(60)(61)(62)(63). Alternatively, AGE-directed therapy can consist of so-called AGE-breakers (64).…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of NEG as a molecular mechanism that contributes to the development of OA provides new opportunities for therapies directed at the prevention of OA by inhibiting or reversing AGE formation. Inhibition of AGE formation by prophylactic treatment with compounds such as aminoguanidine, pyridoxamine, tenilsetam, or simple amino acids (e.g., lysine or arginine) has been shown to prevent AGErelated pathologies such as vascular stiffening, heart collagen accumulation, and protein crosslinking (59)(60)(61)(62)(63). Alternatively, AGE-directed therapy can consist of so-called AGE-breakers (64).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of AGE on tissue proteins has been implicated in the ageing of proteins and the progression of chronic, age-related diseases [1], such as atherosclerosis [2], chronic renal failure [3], Alzheimer's disease [4] and diabetes mellitus [5,6,7,8]. Glucose initially reacts with proteins to form reversible early glycation products.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetes mellitus, AGE accumulation in skin collagen is correlated both with the duration and severity of hyperglycaemia, and with the presence of long-term complications [6,7,8,12,13,14,15]. In a DCCT substudy, skin AGE levels explained 19 to 36% of the variance in the incidence of long-term diabetic complications in intensively treated patients, and 14 to 51% in conventionally treated patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Protein glycation, as well as protein oxidation and nitration, is thought to contribute to vascular cell dysfunction and the development of microvascular diabetic complications (retinopathy, nephropathy and neuropathy) [2][3][4]. Recent research has shown that protein glycation, oxidation and nitration are increased in cellular and ex-tracellular proteins in diabetes [5].…”
Section: Introductionmentioning
confidence: 99%